(Trans)literary chords: discourses, subjectivities, and authorship in Spanish and Latin American songs of the intermedial era (Anclajes, 2026)
The relationship between literature and contemporary Spanish and Latin American song is analysed from an intermedial perspective, drawing on the historical link between words and music and the growing interest in song as a subject of analysis within literary studies. Based on different theoretical approaches, it reviews the main lines of research that have addressed song to date, as both a potential literary text and a complex artistic phenomenon that articulates various semiotic and pragmatic levels. Within this framework, the contributions explore how song establishes dialogues with literature and other cultural fields, paying special attention to the construction of subjectivities, memories, and sociocultural identities, particularly in political contexts, as well as to authorial figurations and the processes of circulation and resignification of the literary dimension in the musical sphere.
Keywords: Music and Literature; Contemporary Spanish Song; Intermediality; Authorial Studies; 20th and 21st Centuries